Prognostic Value of Cell-Surface Vimentin-Positive CTCs in Pediatric Sarcomas - Dao, Long; Ragoonanan, Dristhi; Batth, Izhar; Satelli, Arun; Foglesong, Jessica; Wang, Jian; Zaky, Wafik; Gill, Jonathan B.; Liu, Diane; Albert, Aisha; Gordon, Nancy; Huh, Winston; et al. (Frontiers in Oncology, 2021)
Background Despite advances in care, the 5 year overall survival for patients with relapsed and or metastatic sarcoma remains as low as < 35%. Currently, there are no biomarkers available to assess disease status in patients with sarcomas and as such, disease surveillance remains reliant on serial imaging which increases the risk of secondary malignancies and heightens patient anxiety. Methods Here, for the first time reported in the literature, we have enumerated the cell surface vimentin (CSV+) CTCs in the blood of 92 sarcoma pediatric and adolescent and young adult (AYA) patients as a possible marker of disease. Results We constructed a ROC with an AUC of 0.831 resulting in a sensitivity of 85.3% and a specificity of 75%. Additionally, patients who were deemed to be CSV+ CTC positive were found to have a worse overall survival compared to those who were CSV+ CTC negative. We additionally found the use of available molecular testing increased the accuracy of our diagnostic and prognostic tests. Conclusions Our findings indicate that CSV+ CTCs have prognostic value and can possibly serve as a measure of disease burden.